Complement promotes endothelial von Willebrand factor and angiopoietin-2 release in obstructive sleep apnea. Issue 4 (22nd December 2020) - Gao, Su; Emin, Memet; Thoma, Theodosia; Pastellas, Kalliopi; Castagna, Francesco; Shah, Riddhi; Jimenez, Alondra; Patel, Neha; Wei, Ying; Jelic, Sanja
Abstract: Study Objective: Obstructive sleep apnea (OSA) is highly prevalent and triples vascular thromboembolic risk. Intermittent hypoxia (IH) during transient cessation of breathing in OSA impairs endothelial protection against complement. Complement activation stimulates the endothelial release of a pro-thrombotic von Willebrand factor (vWF). We investigated whether increased complement activity in OSA promotes the endothelial release of vWF and pro-inflammatory angiopoietin-2. We further investigated whether improving complement protection with statins reverses these changes. Methods: Using endothelial cells (ECs) and blood collected from OSA patients ( n = 109) and controls ( n = 67), we assessed whether altered cellular localization of complement inhibitor CD59 in OSA modulates exocytosis of Weibel-Palade bodies (WPB), secretory granules that store vWF and angiopoietin-2. These interactions were also assessed in vitro in ECs exposed to normoxia or IH with or without recombinant complement C9 and with or without atorvastatin. Results: Circulating levels of angiopoietin-2 were greater in OSA than controls and levels of vWF cleavage products correlated with OSA severity. In cultured ECs, IH enhanced complement-stimulated angiopoietin-2 and vWF release by reducing EC surface and increasing intracellular expression of complement inhibitor CD59. Intracellular CD59 co-localized with WPB in OSA. IH increased binding of intracellular CD59 to syntaxin-3, which dissociated syntaxin-3 from voltage-sensitive calcium channel Cav 1.2, and activated WPB exocytosis in a calcium-dependent manner. Atorvastatin reversed IH-enhanced endothelial release of vWF and angiopoietin-2. Conclusions: IH promotes the complement-mediated release of vWF and angiopoietin-2, which may contribute to pro-thrombotic and pro-inflammatory conditions in OSA. Statin reversed these effects, suggesting a potential approach to reduce cardiovascular risk in OSA.